Quality Indicators for Older Persons' Transitions in Care: A Systematic Review and Delphi Process. Issue 1 (3rd March 2022) - Tate, Kaitlyn; Lee, Sarah; Rowe, Brian H; Cummings, Garnet E; Holroyd-Leduc, Jayna; Reid, R Colin; El-Bialy, Rowan; Bakal, Jeffrey; Estabrooks, Carole A; Anderson, Carol; Cummings, Greta G
Abstract: We identified quality indicators (QIs) for care during transitions of older persons (≥ 65 years of age). Through systematic literature review, we catalogued QIs related to older persons' transitions in care among continuing care settings and between continuing care and acute care settings and back. Through two Delphi survey rounds, experts ranked relevance, feasibility, and scientific soundness of QIs. A steering committee reviewed QIs for their feasible capture in Canadian administrative databases. Our search yielded 326 QIs from 53 sources. A final set of 38 feasible indicators to measure in current practice was included. The highest proportions of indicators were for the emergency department (47%) and the Institute of Medicine (IOM) quality domain of effectiveness (39.5%). Most feasible indicators were outcome indicators. Our work highlights a lack of standardized transition QI development in practice, and the limitations of current free-text documentation systems in capturing relevant and consistent data.